Schaum's Feedback and Control Systems Problem 14.18: Root Locus Design Example 1 - Berry, Carlotta A. (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates how to use root locus design to select the gain, K such that a closed loop system has required dominant poles.